2008
DOI: 10.2113/gssgfbull.179.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Paleozoic tectonic evolution of the Yili Block, western Chinese Tianshan

Abstract: The Yili block is a triangular area bordered by sutures and fault zones in the western Chinese Tianshan belt. It is often considered as a part of the Central Tianshan micro-continent with Proterozoic basement extending westward into Kazakhstan and Kirgizstan, but this interpretation is questionable. This paper aims to synthesize the available data, discusses the meaning of the tectonic boundaries and proposes a model for the Paleozoic evolution of the Yili block. Alike the entire Tianshan belt, the Yili block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
184
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(190 citation statements)
references
References 24 publications
5
184
1
Order By: Relevance
“…These assemblages mainly consist of Nb-enriched basalts and adakitic rocks and show typical characteristics of magmas formed in a subduction zone, therefore demonstrating that southward subduction of the Junggar Ocean most likely began during the late Paleozoic (Long et al, 2011a;Tang et al, 2010a;Wang et al, 2006aWang et al, , 2007bWindley et al, 1990;Xiao et al, 2004aXiao et al, , 2008Xiao et al, , 2010Zhang et al, 2009Zhang et al, , 2012Zhu et al, 2012a). This is also supported by extensively exposed late Paleozoic accretionary complexes in the northern part of the Yili Block (Gao et al, 1997;Wang et al, 2008;XBGMR, 1993;Xiao et al, 2010Xiao et al, , 2013. In the middle Ordovician, however, calc-alkaline volcanic rocks interlayered with the marine strata indicate an active margin tectonic setting and reveal that the middle Ordovician is a key period for the southern PaleoAsian Ocean when extension (ocean opening) changed to convergence (ocean closure) (Gao et al, 1997;XBGMR, 1993).…”
Section: The Onset Of Southward Subduction Of the Junggar Oceanmentioning
confidence: 66%
See 3 more Smart Citations
“…These assemblages mainly consist of Nb-enriched basalts and adakitic rocks and show typical characteristics of magmas formed in a subduction zone, therefore demonstrating that southward subduction of the Junggar Ocean most likely began during the late Paleozoic (Long et al, 2011a;Tang et al, 2010a;Wang et al, 2006aWang et al, , 2007bWindley et al, 1990;Xiao et al, 2004aXiao et al, , 2008Xiao et al, , 2010Zhang et al, 2009Zhang et al, , 2012Zhu et al, 2012a). This is also supported by extensively exposed late Paleozoic accretionary complexes in the northern part of the Yili Block (Gao et al, 1997;Wang et al, 2008;XBGMR, 1993;Xiao et al, 2010Xiao et al, , 2013. In the middle Ordovician, however, calc-alkaline volcanic rocks interlayered with the marine strata indicate an active margin tectonic setting and reveal that the middle Ordovician is a key period for the southern PaleoAsian Ocean when extension (ocean opening) changed to convergence (ocean closure) (Gao et al, 1997;XBGMR, 1993).…”
Section: The Onset Of Southward Subduction Of the Junggar Oceanmentioning
confidence: 66%
“…Silurian arc-related calc-alkaline volcanic rocks, volcanic-sedimentary rocks and flysch are also observed in the northern part of the KYB and in the central part of the NMT (Gao et al, 1997;Wang et al, 2008;XBGMR, 1993). Late Paleozoic to Mesozoic strata are widely distributed in the northwestern Tianshan, and most have Devonian to Carboniferous ages.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one is the age of the orogeny which some authors considered as to be late Paleozoic (e.g., Gao et al, 1998Gao et al, , 2009Wang et al, 2010) but, alternatively, others ague for Triassic (e.g., Zhang et al, 2007;Xiao et al, 2008). The second issue concerns the polarity of subduction of the paleo-Tianshan Ocean, a north-directed subduction was proposed by Windley et al (1990), Xiao et al (2004Xiao et al ( , 2008, Gao et al (1998) and Gao and Klemd (2003); whereas, a southward subdution is more likely consistent with newly published data (Charvet et al, 2007;Wang et al, 2008;Lin et al, 2009); and a compromise of bi-directional subduction was suggested by Gao et al (2009).…”
Section: Introductionmentioning
confidence: 84%